SOCIOLOGY OF KNOWLEDGE SECURITY IN THE DIGITAL EDUCATIONAL SPACE - M. Yu. Zakharov; I. E. Starovoytova; A. V. Shishkova (Вестник университета)
The article deals with the spread of digital technologies in education and digital learning as a special stage of digital socialization, changing the social roles of the teacher and student. Artificial intelligence and machine learning technologies, big data analysis, robotics and virtualization have taken their place in the educational process, and traditional offline teaching methods require revision. The problem of knowledge alienation in the digital educational space has been analysed and ways to solve this problem have been proposed. Particular attention has been paid to the problem of the safety of knowledge in the educational space. It has been concluded about the need for such a reorganization of the digital space in which cognitive conditions for the safe functioning of knowledge will be provided.